FEATURES OF SOCIOCULTURAL COMPONENTS OF SCHOOL GEOGRAPHY EDUCATION - Palamarchuk, Larisa B. (Educological discourse, 2015)
In the article reveals functions of socio-cultural component of geographical education in modern school. The socio-cultural component of geography school course is a priority in today's educational process. Among main function of socio-cultural component of school education geographical content we underline: cognitive, information, communication, value-orientation, normative and regulative functions. Socio-cultural features aimed at the development of the material and spiritual life of society, where the secondary school has a crucial role. It not only has a direct influence on the formation of personality, but also provides a sense of social responsibility helps to save, develop, translate spiritual and material heritage. The socio-cultural component of Geography school course content affects not only the cognitive side of students’ self-disciple, but also promotes formation of ideals, values, self-esteem. In Geography classes precede formation of national citizen conscious, patriot, careful owner, educated person, humanist and naturalists. It raises an ability by cooperation during the tour, doing practical work and designing collective work - report. Geographical image of native land, imagined by students, creates a solid basis for learning of homeland Geography, the mainland, parts of the world, and the entire planet. The ability to see the uniqueness of native land forms students as cultural patriot citizen. According to the requirements of the time, the interest to sociocultural competence of human grows, so grows the relevance of this educational problem.